Simultaneous measurement of extracellular dopamine and dopamine transporter occupancy by cocaine analogs in squirrel monkeys - Kimmel, Heather L. (2012)
Several classes of drugs bind to the dopamine transporter (DAT) with high affinity, but some are weaker positive reinforcers than cocaine, suggesting that affinity for and occupancy of the DAT is not the only determinant of a drug’s reinforcing effectiveness. Other factors such as the rate of onset have been positively and strongly correlated with the reinforcing effects of DAT inhibitors in nonhuman primates. In the current studies, we examined the effects of acute systemic administration of cocaine and three cocaine analogs (RTI-150, RTI-177, and RTI-366) on binding to DAT in squirrel monkey brain using PET neuroimaging. During the PET scan, we also measured drug effects on dopamine (DA) levels in the caudate using in vivo microdialysis. In general, our results suggest a lack of concordance between drug occupancy at DAT and changes in DA levels. These studies also indicate that acute cocaine administration decreases the availability of plasma membrane DAT for binding, even after cocaine is no longer blocking DA uptake as evidence by a return to basal DA levels.